(untitled) (Journal of Comparative & International Higher Education, 2024)
Although it is a highly developed industrial country and generally known as technologically savvy, Germany lags internationally in digital transformation. Moreover, Germany’s progress in Higher Education (HE) is uneven since 16 federal states have responsibility for education, including Higher Education. The pandemic has reinforced the importance as much as accelerated the transition to digitalization in HE. Although HE leaders see digitalization as important for research, service, and management, they emphasize that digital transformation has meaning for teaching and learning. The new digitally-based formats of teaching and learning—for example “blended learning” and so-called “inverted classroom” formats—benefit students most as they motivate and engage them more than does traditional classroom-based education. As Germany is a member of the European Union (EU) and a signatory of the Bologna Process, European policies, programs, guidelines, and agreements also affect Germany’s digital transformation.